Employee Work Behavior in Creative Industries - Savitri, Nilasari; Phelia, Anisya; Iskandar, Amir; Maharani, Anita (Open Access Indonesia Journal of Social Sciences, 2021)
This study aims to determine the effect of thinking style, integrity, and meaning of work on counterproductive work behavior in creative industries. The concept in explaining phenomenon start from elaboration from each of the keywords mentioned: thinking style, integrity, work meaning, and counterproductive behavior. The research method used in this research is explanatory research. The data used are primary. The population in this study is the entire creative industry sector in Indonesia. This research model is multivariate using SPSS as an analytical tool in this research. The results showed partially and simultaneously that the style of thinking, integrity, and meaning of work did not affect counterproductive behavior. So we can conclude that this study shows that if there is counterproductive behavior in employees in the creative industry who have a more open-minded pattern but no influence from thinking style, integrity, and work meaning.